Roberto Tottoli (2023). Studies in Islamic Traditions and Literature. London: Routledge. 284 Pages. ISBN 978-0-367-53166-9 (hbk) - Kafi, Fina Aunul (Journal of Al-Tamaddun, 2025)
In modern Islamic studies, insights into the early foundations of Islam and beliefs derived from Islamic traditions (ḥadīth) and historical accounts have become increasingly significant. In the era of globalization and the development of information technology, Islamic traditions are often reinterpreted in various contexts, both academic and non-academic, along with the potential to give rise to distortions of the main reference of Islam. So with the increase in academic studies of Islam in various parts of the world, there is a need to review how Islamic tenets develop through Islamic traditions and historical reports that shape Muslims' perception of religious values and norms. In the midst of an ever-changing Islamic narrative, accurate insights into Islamic traditions and historical data can be a fortress against bias, simplification, and doctrinal influence.